Kompensasi Pegawai Outsourcing Di Pt. Pln (Persero) Unit Induk Wilayah Sulselrabar - Indhi, Indhi; Tahir, Nurbiah; Arfah, Sitti Rahmawati (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of this research is to find out how the outsourcing employee compensation system from PT. Tamesti Palikssa Sejahtera who was placed at PT. PLN (Persero) Unit Induk Wilayah Sulselrabar. This study uses descriptive qualitative research and data collection techniques used are interviews, observation and documentation. The results of the study, PT. Tamesti Palikssa Sejahtera in this case the leadership of PT. Tamesti Palikssa Sejahtera pays little attention to the welfare of outsourcing employees. This is very unfavorable for the outsourcing employees because the amount of compensation that is lacking starting from overtime work is still there but oevertime pay is eliminated, and tips are also only given from the kindness of the permanent employees at PT. PLN (Persero) Unit Induk Wilayah Sulselrabar, granting leave for whichthe salaries of outsourcing employees will begin to be deducted when the maximum limit of 5 days for employee permission to take leave is ranted, and operational vehicle facilities are not provaded to outsourcing employees.  Keywords: Compensation, Outsourcer